Dampak Penggunaan Media Pembelajaran Inovatif terhadap Peningkatan Pemahaman Konsep Akuntansi bagi Mahasiswa di Universitas 17 Agustus 1945 Surabaya - Patricia Channelia Wea; Hwihanus Hwihanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study analyzes the impact of innovative learning media on students' understanding of accounting concepts at the University of 17 August 1945 Surabaya. Using a qualitative approach, data were collected through in-depth interviews and participatory observations involving lecturers and students. The study examined media such as business simulations, animated videos, and case-based applications. Findings reveal that innovative learning media enhance student participation, simplify complex accounting concepts, and improve practical skills. Additionally, interactions between lecturers and students became more dynamic and engaging. Despite these benefits, challenges like limited technological resources and the need for adaptation time remain obstacles. This study highlights the importance of developing and integrating educational technology to support effective and relevant accounting learning.